SYSTEM-PARAMETRIC ASSESSMENT OF THE EFFICIENCY OF ELECTRICITY CONSUMPTION BY IRON ORE ENTERPRISES - BERIDZE, TETIANA; KASATKINA, IRINA; BOYKO, SERHIY; VYSHNEVSʹKYY, SVIATOSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The components of electricity consumption by iron ore enterprises are generalized and studied. On the basis of systematicity, a mathematical model has been built that allows developing a methodology for assessing the efficiency of electricity consumption under a three-zone tariff grid. The mathematical modeling of electricity consumption by iron ore enterprises as a complex object makes it possible to numerically determine the impact of the value of electricity consumption on the cost of electricity consumption by an iron ore enterprise. This approach made it possible to obtain quantitative indicators of the efficiency of electricity consumption at specific iron ore enterprises. The methodology for assessing the efficiency of electricity consumption at iron ore enterprises was further developed. For the first time, a model for assessing the efficiency of electricity consumption under a three-zone tariff grid was formulated and built. The proposed methodology can be used as a basis for unifying the quantitative assessment of electricity consumption efficiency. The analysis of the results makes it possible to conduct a quantitative and qualitative assessment of the efficiency of electricity consumption processes on the basis of system-parametric modeling for iron ore enterprises. The developed methodology can be unified for implementation at iron ore enterprises of the national economy. It is advisable to include the developed model in the practice of relevant calculations of the economic activity of iron ore enterprises. It has been established that in the current conditions of functioning of iron ore enterprises it is advisable to study the consumption of electricity as a systemic complex object. The carried out analysis made it possible to build an objective function that takes into account the consumption of electricity by ore intake devices depending on the time of day